Unveiling the Meaning and Factors of Marriage Happiness: A Phenomenological Study of Toba Batak Couples - Samosir, Chindy Theresia; Nurhayati, Siti Rohmah (World Psychology, 2025)
Marital happiness can be influenced by culture because there are cultural values that play a role in encouraging individual happiness. The purpose of this study is to explore the meaning of marital happiness for Toba Batak couples and determine what factors influence marital happiness for Toba Batak couples. The method used in this study is a qualitative method with a phenomenological approach. This research was conducted in Marindal I village, Patumbak District, Deli Serdang Regency, North Sumatra, which was conducted from March to April 2024. This study took four Toba Batak couples. The data collection procedure used in-depth interviews with a semi-structured form. The data analysis technique used was reading the data that had been obtained, organizing the data, and determining the theme. The results found that the meaning of marital happiness for the Toba Batak tribe when having children is increasingly complete with the presence of grandchildren so that they can perfect the lineage. It was also found that the factors that influence marital happiness for the Toba Batak tribe are internal factors consisting of communication and economics, while external factors consist of neighborly harmony and activeness in the community. Each culture influences marital happiness, so the meaning of marital happiness in each region will be different from one another.